Protocol for evaluation of iTEST, a novel blended intervention to enhance introspective accuracy in psychotic disorders - Sarah A. Berretta; Nicole Abaya; Emma Parrish; Lauren E. McBride; Raeanne C. Moore; Robert Ackerman; Philip D. Harvey; Amy E. Pinkham; Colin A. Depp (NPP-Digital Psychiatry and Neuroscience, 2025)
Abstract Poor introspective accuracy (IA), defined as inaccurate judgments of one’s abilities and performance, is a strong and independent predictor of functional impairment in people with psychotic disorders. However, there are currently no treatments that directly target IA in this population as a primary outcome. We describe a protocol for a clinical trial to test a newly developed blended digital intervention, Improving Thinking through Everyday SelfAssessment Training (iTEST), aimed at improving IA in people with psychotic disorders to improve functional outcomes. iTEST involves daily training consisting of feedback on IA in mobile cognitive tests, coupled with individual coaching that applies improved IA to participant-identified recovery goals. Following the NIMH experimental therapeutics paradigm, the first step in the evaluation of iTEST is an open trial in 60 individuals with psychotic disorders to assess 1) feasibility and acceptability, and 2) whether the intervention leads to clinically significant improvement in an objective target: IA on trained tasks along with transfer to an untrained task-based measure of IA. After programming of the mobile intervention and the creation of treatment manuals, enrollment for an open trial started in November 2023 and will be completed by April 2025. If effective, iTEST could be integrated with cognitive training and other rehabilitative interventions to boost the impact on functional outcomes. Trial registration: ClinicalTrials.gov NCT05899348.